Mechanism of a novel Bacillus subtilis JNF2 in suppressing Fusarium oxysporum f. sp. cucumerium and enhancing cucumber growth - Yang, Fan; Wang, Xin; Jiang, Huayan; Yao, Qiuju; Liang, Shen; Chen, Weiwei; Shi, Gongyao; Tian, Baoming; Hegazy, Abeer; Ding, Shengli (Frontiers in Microbiology, 2024)
Cucumber Fusarium wilt caused by Fusarium oxysporum f. sp. cucumerium (FOC), is a prevalent soil-borne disease. In this study, Bacillus subtilis JNF2, isolated from the high incidence area of cucumber Fusarium wilt in Luoyang, demonstrated significant inhibitory effects on FOC and promoted cucumber seedling growth. The biocontrol mechanism of strain JNF2 were elucidated through morphological observation, physiological and biochemical experiments, and whole genome sequence analysis. Pot experiments revealed an 81.33 ± 0.21% control efficacy against Fusarium wilt, surpassing the 64.10 ± 0.06% efficacy of hymexazol. Seedlings inoculated with JNF2 exhibited enhanced stem thickness and leaf area compared to control and hymexazol-treated plants. Physiological tests confirmed JNF2’s production of indole-3-acetic acid (IAA), siderophores, and hydrolytic enzymes, such as β-1,3-glucanase, amylase, and protease, which inhibited FOC growth and promoted plant development. Genome analysis identified genes encoding antimicrobial peptides and hydrolases, as well as a novel glycocin synthetic gene cluster. These findings underscore B. subtilis JNF2’s potential as a biocontrol agent for sustainable cucumber cultivation.